An ambient agent model for analyzing managers’ performance during stress - Che Pa, Noraziah; Ab. Aziz, Azizi; Gratim, Haned (2016)
Stress at work have been reported everywhere.Work related performance during stress is a pattern of reactions that occurs when managers are presented with work demands that are not matched with their knowledge, skills, or abilities, and which challenge their ability to cope.Although there are many prior findings pertaining to explain the development of manager performance during stress, less attention has been given to explain the same concept through computational models.In such, a descriptive nature in psychological theories about managers’ performance during stress can be transformed into a causal-mechanistic stage that explains the relationship between a series of observed phenomena.This paper proposed an ambient agent model for analyzing managers’ performance during stress.Set of properties and variables are identified through past literature s to construct the model.Differential equations have been used in formalizing the model.Set of equations reflecting relations involved in the proposed model are presented. The proposed model is essential and can be encapsulated within an intelligent agent or robots that can be used to support managers during stress.